2010
DOI: 10.1007/s10529-010-0225-9
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic analysis of elicited cell suspension cultures of Cannabis sativa L. by 1H-NMR spectroscopy

Abstract: Cannabis sativa L. plants produce a diverse array of secondary metabolites. Cannabis cell cultures were treated with jasmonic acid (JA) and pectin as elicitors to evaluate their effect on metabolism from two cell lines using NMR spectroscopy and multivariate data analysis. According to principal component analysis (PCA) and partial least square-discriminant analysis (PLS-DA), the chloroform extract of the pectin-treated cultures were more different than control and JA-treated cultures; but in the methanol/wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In hemp suspension cells, elicitation with biotic and abiotic elicitors did not induce an increase in cannabinoids ( Flores-Sanchez et al, 2009 ); however, jasmonic acid was shown to elicit the production of the antioxidant tyrosol ( Pec et al, 2010 ).…”
Section: Cannabis Biotechnology: Challenges and Prospectsmentioning
confidence: 99%
“…In hemp suspension cells, elicitation with biotic and abiotic elicitors did not induce an increase in cannabinoids ( Flores-Sanchez et al, 2009 ); however, jasmonic acid was shown to elicit the production of the antioxidant tyrosol ( Pec et al, 2010 ).…”
Section: Cannabis Biotechnology: Challenges and Prospectsmentioning
confidence: 99%
“…In this work, several compounds were tested on cell suspensions obtained from the industrial hemp variety Futura to identify the best elicitor treatment that is able to induce secondary metabolism and to elucidate the metabolic pathways activated by the elicitation. The elicitors were chosen based on results achieved both on cannabis cell cultures [18] and on other species ([19] and references therein). Namely, CHT, SA, JA, and MeJA were tested in this study, as well as a combination of elicitation and precursor feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of tyrosol, an antioxidant compound mainly found in olive oil and in plants of the Rhodiola species, was described for the first time in cell suspensions of a drug-type hemp variety by Peč et al [18]. These authors obtained two types of cell lines, green and greenish-brown cells, that produced more tyrosol than olive oil after JA elicitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This method had been successfully used to differentiate Cannabis cultivars [14]. Moreover, 1 H-NMR based-metabolomics had been applied to study the impact of elicitation in cell suspension cultures of Cannabis [15][16]. Our previous work also applied 1 H-NMR-based metabolomics that combined with real time PCR (RT-PCR) technique for studying cannabinoid biosynthesis of Cannabis cultivars over flowering season [17].…”
Section: ■ Introductionmentioning
confidence: 99%